MYELOLIPOMA IN THE ADRENAL GLAND OF A CANINE - Togni, Monique (2020)
The present report aims to describe the macroscopic and histopathological findings of a canine with myelolipoma in the left adrenal gland. Although the adrenal gland tumors are frequently found in dogs, myelolipomas are generally found in cattle or primates and uncommon in other species. A corpse of a mixed-breed canine, with a clinical diagnosis of acute kidney disease, was referred to the Pathology Laboratory for necropsy. At the opening of the abdominal cavity, a vascular mass medial to the left edge surrounding the renal hilum was detected. The left kidney had a higher volume. The mass was microscopically diagnosed as myelolipoma, and changes were found in the left kidney, suggesting renal ischemia. The diagnosis of adrenal myelolipoma was considered an incidental necropsy finding, which was the cause of the death of this canine, while the origin of the bilateral kidney disease was not provided. Although this tumor was not directly related to the death of the animal compatible with ischemia in the left border, benign adrenal tumors, such as myelolipoma, could generate compression at the border.